2017
DOI: 10.1016/j.ejmech.2017.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Indole carboxylic acid esters of melampomagnolide B are potent anticancer agents against both hematological and solid tumor cells

Abstract: A series of novel, heteroaryl carboxylic acid conjugates of the sesquiterpene melampomagnolide-B (MMB, 3) has been evaluated as antitumor agents against an NCI panel of 64 human hematopoetic and solid tumor cell lines. The indole-3-acrylic acid conjugate 7j and the indole-3-carboxylic acid conjugate 7k were found to be the most potent analogs in the series. Compounds 7j and 7k exhibited remarkable growth inhibition, GI50 values in the range 0.03–0.30 μM and 0.04–0.28 μM, respectively, against the cell lines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Based upon the results from this study, potential new combinations of ActD with the abundantly available sesquiterpene lactones and their analogs are worthy of investigation to determine whether synergistic drug combinations can be achieved. A number of newer sesquiterpene lactone‐based drugs have been developed which are more cytotoxic to cancer cells than either DMAPT or PTL (Bommagani et al, ; Janganati, Ponder, Thakkar, Jordan, & Crooks, ). This might lead to numerous opportunities for exploring combination drug treatment regimens of ActD with these newer SLs.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the results from this study, potential new combinations of ActD with the abundantly available sesquiterpene lactones and their analogs are worthy of investigation to determine whether synergistic drug combinations can be achieved. A number of newer sesquiterpene lactone‐based drugs have been developed which are more cytotoxic to cancer cells than either DMAPT or PTL (Bommagani et al, ; Janganati, Ponder, Thakkar, Jordan, & Crooks, ). This might lead to numerous opportunities for exploring combination drug treatment regimens of ActD with these newer SLs.…”
Section: Discussionmentioning
confidence: 99%
“…U-251 MG is an established GBM cell line [ 15 ], part of the NCI-60 human cancer cell lines [ 25 ], with the ability to form spheroids with invasive properties [ 26 ]; it has been used in the screening of pharmaceutical agents to identify, characterize, and select novel compounds with growth inhibition and/or killing of tumor cells. A series of 22 different compounds called BS, BSK, JVM PNR, and ST [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] whose the chemical structures, details, and activity are explained in Table 1 and Figure S1 , were incubated with the spheroids for 48 h to define the toxicity the effects on their invasiveness. These compounds have anti-invasive properties, as they interfere with pathways of cell invasion ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The reported SAR studies of PTL indicated that α,β-unsaturated ketone and double bond C1C10 are the essential pharmacophores, and modifications on the 14-methyl group are beneficial to the cytotoxicity of PTL. , Research suggested that heterocycles might cause stacking interactions between ligands and proteins . To explore the SAR relationship between PTL and PKM2, three routes were outlined (Scheme ) in this study.…”
Section: Resultsmentioning
confidence: 99%